Analysis of the Effect of Climate Change on Biodiversity Conditions in West Nusa Tenggara - Jupri, Ahmad; Ahyadi, Hilman; Uzma, Saadatul; Muthma'innah, Elfira; Riski, Tita Nia Ananda; Hakim, Abdurrahman; Wulandari, Suci Yulia; Hidayah, Nurul (Jurnal Biologi Tropis, 2024)
West Nusa Tenggara has a high level of fauna (animal) characteristics, because its position is on the Wallacea line as an ecological transition between the continents of Asia and Australia. The fauna in NTB varies according to the existing ecosystem, this happens because there is a match between the species and the environment or place where they develop. An ecosystem that experiences changes in certain conditions can also cause changes in species variations. Climate change is one of the causes of changes in an ecosystem. This research aims to determine the impact of climate change on biodiversity conditions in NTB. Research activities were carried out at the offices of the NTB Environment and Forestry Service, the NTB Natural Resources Conservation Center, and the NTB Maritime and Fisheries Service, for interviews and requests for data regarding climate change and diversity in NTB. The research method used was purposive sampling. The results of animal data show that this species already has a small number in NTB so it must be immediately conserved by the local government so that it does not experience extinction due to climate change.